Covid-19 And Religion: Response Believers About Online Service - Tari, Ezra; Wijaya, Hengki; Weismann, Ivan Th. (AL-ADYAN, 2021)
Covid-19 provides lessons for society, especially believers. The real fellowship must be limited, and online worship held, making believers enter a new atmosphere. The challenge is not whether it can or not, but financial issues and including the internet are a concern in the Indonesian context. The purpose of this article is to show the church around the ministry during the pandemic. The research method used is a qualitative interview of individuals involved in worship, both online and offline. This study reveals that each church has differences in managing religious life because the existing tradition and ecclesiology make it difficult for the church to accomplish the ministry. The church tries to communicate with the congregation using modern technology or go straight to the houses while still following the government's recommendations, namely social distancing and attention to health. The church must begin to think about the pattern of fellowship today.